2017
DOI: 10.1126/science.aal2690
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping memory trace indispensable for linking, but not recalling, individual memories

Abstract: Memories are not stored in isolation from other memories but are integrated into associative networks. However, the mechanisms underlying memory association remain elusive. Using two amygdala-dependent behavioral paradigms-conditioned taste aversion (CTA) and auditory-cued fear conditioning (AFC)-in mice, we found that presenting the conditioned stimulus used for the CTA task triggered the conditioned response of the AFC task after natural coreactivation of the memories. This was accompanied through an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 33 publications
7
87
1
Order By: Relevance
“…These studies first demonstrated that a shared amygdala ensemble encodes two auditory fear memories that are acquired close in time (within 6 h) and that these memories are linked 46 . Researchers demonstrated the specific role of such shared neuronal ensembles by silencing them, which affected the behavioral interaction of two amygdala-dependent tasks but did not interfere with the retrieval of individual tasks 47 .…”
Section: Functions Of the Cell-wide Increase In Excitabilitymentioning
confidence: 99%
“…These studies first demonstrated that a shared amygdala ensemble encodes two auditory fear memories that are acquired close in time (within 6 h) and that these memories are linked 46 . Researchers demonstrated the specific role of such shared neuronal ensembles by silencing them, which affected the behavioral interaction of two amygdala-dependent tasks but did not interfere with the retrieval of individual tasks 47 .…”
Section: Functions Of the Cell-wide Increase In Excitabilitymentioning
confidence: 99%
“…With associative memory cells in the sensory cortices 1, 3, 7, 16 , their axon-innervated downstream brain cells are able to encode these associated signals 1720 . The stimulations to any of these areas in the neural circuits from sensory cortices to behavior- and emotion-controlled brain nuclei can induce memory presentation 2127 .…”
Section: The Cellular Mechanism Underlying Associative Memorymentioning
confidence: 99%
“…For memory integration to occur, a new event that overlaps with prior experience (e.g., meeting the husband) must trigger reactivation of a prior related episode (initially meeting the woman and her son); new information may then be integrated into the reactivated memory (connecting the boy with his father in memory) [1, 6]. As a result of integration, the two events are represented with overlapping neural codes, in which elements common to both events act as nodes linking the two memories [7, 8]. Such links allow representation of information beyond direct experience and can support flexible behaviors [1], such as taking a shortcut between places in a new town.…”
Section: Introductionmentioning
confidence: 99%